نموذج مقترح لقياس درجة الموهبة باستخدام المنطق الضبابي (دراسة تطبيقية - طلاب الماجستير في كلية العلوم) (Latakia University Journal -Basic Sciences Series, 2017)
للعمل على تطوير البحث العلمي واختيار الأشخاص الموهوبين من طلاب الدراسات العليا (الماجستير) للاستمرار ونيل درجة الدكتوراه في جامعة تشرين. فقد تم إعداد هذا البحث الذي يهدف إلى اقتراح نموذج لقياس درجة الإبداع والموهبة عند طلاب الدراسات العليا باستخدام إحدى تقنيات الذكاء الصنعي ممثلة بالمنطق الضبابي. لقد تم بناء نظام خبير يحوي قاعدة استدلال تتضمن ثلاثة أنواع من الاختبارات: الاختبار النظري، الاختبار العملي, اختبار الإبداع في كل مقرر دراسي. كما هدف هذا النظام الذكي إلى تحديد القدرة على اتخاذ القرار والذي يعطي نسبة الموهبة عند طلاب الدراسات العليا. وقد توصلت الدراسة إلى مجموعة هامة من النتائج من أهمها الآتي: أظهرت النتائج قوة وموثوقية عالية تبين مصداقية عمل هذا النموذج المقترح حيث وصلت صدقية النتائج بين 85% و100% وذلك باستخدام طريقتين مختلفتين لفك تضبيب النموذج المقترح. This study has been done to develop scientific research and select talented people of post-graduate students (master students) to continue and get doctoral degrees (degree in PHD) at Tishreen University. The research has been prepared, which aims to suggest a model for measuring the degree of creativity and talent for post-graduate students by using one of artificial intelligence techniques such as Fuzzy Logic.An expert system has been built that contains an inference rule which consists of three types of tests: (Theory Test, TT), (Practice Test, PT), and (Creativity Test, CT) for each course.This intelligent system has also aimed to determine the ability to make decisions which gives the rate of talent for post- graduate students.The study has reached to an important set of results, and the most important is: Results have shown high strength and reliability shows the validity of this proposed model, the validity of the results have reached to 85% and 100%, by using two different methods to defuzzificate of proposed model.